Tantangan Dan Prospek Dalam Penerapan Prinsip Maqasid Al-Shariah Dalam Konteks Hukum Islam Kontemporer - Syafrianto Syafrianto; Mahyudin Ritonga (Institut Agama Islam Sumatera Barat, 2024)
This article discusses the challenges and prospects in the application of Maqasid al-Shariah principles in the context of contemporary Islamic law, using qualitative research methods and a library research approach. This research aims to explore the role of Maqasid al-Shariah as the main framework in compiling Islamic law that is relevant to the times. The results show that the application of Maqasid al-Shariah aims to maintain the relevance of Islamic law, answer various modern challenges, and realise the benefit of the people. Maqasid al-Shariah principles, such as the protection of religion, soul, mind, offspring, and property, provide flexibility for Islamic law to be applied in various fields, including legislation, economics, health, human rights, and environmental conservation. However, the research also identifies a number of significant challenges, including the lack of a comprehensive understanding of Maqasid al-Shariah among practitioners and policymakers, resistance to legal reform due to rigid textual interpretation, the gap between Maqasid theory and implementation in positive law in Muslim countries, and the influence of globalisation and technological developments that raise new legal issues. On the other hand, this research confirms the great prospect of applying Maqasid al-Shariah to create an inclusive, adaptive and relevant Islamic legal system. The Maqasid-based approach enables Islamic law to provide fair and beneficial solutions to modern society, without compromising the core values of Shari'ah. This shows that Maqasid al-Shariah is a dynamic foundation for realising justice and benefit in various aspects of Muslim life.